e-Journal of business education & scholarship of teaching e-JBEST. - Australian Business Education Research Association ([Mapleton, Qld.] : [e-JBEST], 2007)
From journal home page: The e-Journal of Business Education & Scholarship of Teaching is dedicated to promoting the development of teaching and research in business education internationally. The journal is a forum for the expression of ideas, opinions and research informing the scholarship of teaching and is the official journal of the Australian Business Education Research Association.
Official journal of the Australian Business Education Research Association.
Description based on: Volume 1, issue 1 (2007); title from journal home page (publisher's Web site, viewed July 21, 2014).
Latest issue consulted: Volume 8, issue 1 (2014) (viewed July 21, 2014).
Keywords: Business education -- Australia -- Periodicals; Business education; Australia; Electronic journals